Influence of inlet mass flow rate upon nutrient removal potential for different floating treatment island configurations in a stormwater pond - Urbanek, Vinicius Neves (2021)
Floating Treatment Islands (FTI) are a relatively new technology, that can be used for water treatment. To evaluate the influence of hydrodynamics over nutrient removal potential of FTI in a stormwater pond, a numerical study was undertaken, evaluating the mass removal under different inlet flow rates and root depths. Simulations were performed using an academic version of the commercial software ANSYS CFX. A brief literature review is presented, to show the main topics studied in the FTI research field, and the gaps that this work aims to fill. Then, numerical studies to evaluate how a Pond+FTI system responds to the variation of inflow under different island positioning configurations are presented. Finally, different root depths under the same inflow condition were tested, to establish a relationship between roots, hydrodynamics and treatment by the FTI. We found that the occurrence of recirculation zones nearest to the FTI favors an enhancement of the fraction of mass entering the root zones, and it is the key hydrodynamic aspect of mass removal by these systems. The systems that performed better presented average velocity between 0.08 and 0.10 m/s inside the pond, with reversed flow patterns in the region of the FTI’s roots, conditions that favored both hydraulic residence time and pollutant availability at the root zones. Also, the FTI system presented its best removal performance for relative root depths above 0.45, with an optimal condition being the relative root depth about 0.50, under the perspectives of treatment, hydrodynamics and technical & economic viability.